Functional MRI correlates of lower limb function in stroke victims with gait impairment. - Enzinger, C; Johansen-Berg, H; Dawes, H; Bogdanovic, M; Collett, J; Guy, C; Ropele, S; Kischka, U; Wade, D; Fazekas, F; Matthews, P (2008)
BACKGROUND AND PURPOSE: Although knowledge concerning cortical reorganization related to upper limb function after ischemic stroke is growing, similar data for lower limb movements are limited. Previous studies with hand movement suggested increasing recruitment of motor areas in the unlesioned hemisphere with increasing disability. We used ankle movement as a lower limb analog to test for similarities and differences in recovery patterns. METHODS: Eighteen subjects were selected with chronic residual gait impairment due to a single subcortical ischemic stroke. Functional MRI scans were obtained at 3.0 T during active and passive ankle dorsiflexion in the patients (8 females, 10 males; mean age, 59.9+/-13.5 years; range, 32 to 74 years) and 18 age-matched healthy control subjects. RESULTS: We observed substantial neocortical activity associated with foot movement both in the patients with stroke and in the healthy control subjects. Our primary finding was increased cortical activation with increasing functional impairment. The extent of activation (particularly in the primary sensorimotor cortex and the supplementary motor area of the unlesioned hemisphere) increased with disability. The changes were most prominent with the active movement task. CONCLUSIONS: Using ankle movement, we observed increased activation in the unlesioned hemisphere associated with worse function of the paretic leg, consistent with studies on movement of paretic upper limbs. We interpret this finding as potentially adaptive recruitment of undamaged ipsilateral motor control pathways from the supplementary motor area and (possibly maladaptive) disinhibition of the ipsilateral sensorimotor cortex.